AB0319 Treatment with tocilizumab improved rheumatoid arthritis patients clinically and structurally regardless of the prior use of anti-tnf biologics in daily clinical practice. (23rd January 2014) - Izumi, K.; Kaneko, Y.; Yasuoka, H.; Seta, N.; Kameda, H.; Kuwana, M.; Takeuchi, T.
Abstract : Objectives: To explore the radiographic efficacy of tocilizumab (TCZ) in rheumatoid arthritis (RA) patients with or without the prior use of anti-tumor necrosis factor (TNF) agents in daily clinical practice. Methods: Of a total of consecutive 115 RA patients initiating TCZ treatment in Keio university hospital from July 2008 to March 2011, 46 patients who had x-rays of the both hands and feet were assessed stratified by the use of prior biologics (BIO+) and no use of them (BIO-). They received 8 mg/kg of TCZ every 4 weeks, and were observed for 52 weeks to evaluate the clinical and structural outcomes. Results: Baseline patient characteristics (BIO+, BIO-) were as follows: mean age of 54.8±11.2 years, 52.5±12.5 years; mean disease duration of RA of 6.8±6.5 years, 4.0±3.4 years; concomitant use of methotrexate in 76.9%, 48.5% and use of concomitant glucocorticoid was in 46.2%, 36.4%. Baseline patients' characteristics were comparable between BIO+ and BIO- groups except for ESR (65.9±32.3 in BIO+ vs 42.4±35.3 in BIO-). In BIO+ and BIO- patients, DAS28 remission (DAS28-ESR < 2.6) was achieved in 61.5% and 81.8%, SDAI remission in 38.5% and 54.5%, CDAI remission 38.5% and 51.5%, respectively. Radiographic remission (Δmodified Total Sharp Score ≦0.5) was 46.2% (6/13) in BIO+ patients and 66.7% (22/33) in BIO- patients. There were no significant differences in clinical and structural remission rates between the two groups. Conclusions: The treatment with TCZ improved RA patients clinically and structurally regardless of the prior use of anti-TNF biologicsin daily clinical practice. Disclosure of Interest: None Declared